Psychoform and somatoform dissociation in anorexia nervosa: A systematic review. (2nd November 2020) - Longo, Paola; Panero, Matteo; Amodeo, Laura; Demarchi, Matilde; Abbate‐Daga, Giovanni; Marzola, Enrica
Abstract : Dissociation is a debilitating condition often present as comorbidity in patients with eating disorders, but to date only sparse findings are available on this topic. Additionally, very little data exist on the classification of dissociation, namely, psychoform and somatoform, in anorexia nervosa (AN). This review aimed to provide an updated view on the literature about dissociation in AN, with a focus on AN subtypes (i.e., restricter and binge‐purging) as well as dissociation type (i.e., psychoform and somatoform), when available. We screened 304 studies, and after title and abstract selection and full‐text reading, 29 of them were included in this review. Most of the studies investigated psychoform dissociation, whereas just four publications considered somatoform dissociation. Dissociation resulted to be present in AN more than in healthy controls and in individuals with other psychiatric disorders, and it was related mostly to the binge‐purging subtype of AN. Moreover, dissociation was linked to traumatic events, self‐harm and negative treatment outcomes, especially in patients affected by the binge‐purging subtype of AN. However, results on these matters are scarce and partially discordant. The methodological assessment we performed revealed an overall fair quality of the included studies, although several flaws emerged as well. The present review reported on one hand the relevance of dissociation in AN, but on the other hand the need to stimulate the scientific debate on (a) a deeper investigation of somatoform dissociation in AN and (b) the relationship between dissociation and both clinical severity and treatment response/resistance in AN.